The Human Microbiota in Endocrinology: Implications for Pathophysiology, Treatment, and Prognosis in Thyroid Diseases - Docimo, Giovanni; Cangiano, Angelo; Romano, Roberto Maria; Pignatelli, Marcello Filograna; Offi, Chiara; Paglionico, Vanda Amoresano; Galdiero, Marilena; Donnarumma, Giovanna; Nigro, Vincenzo; Esposito, Daniela; Rotondi, Mario; Candela, Giancarlo; et al. (Frontiers in Endocrinology, 2020)
The human microbiota is an integral component in the maintenance of health and of the immune system. Microbiome-wide association studies have found numerous diseases associated to dysbiosis. Studies are needed to move beyond correlations and begin to address causation. Autoimmune thyroid diseases (ATD) are one of the most common organ-specific autoimmune disorders with an increasing prevalence, higher than 5% worldwide. It mainly manifests as Hashimoto's thyroiditis and Graves’ disease. The exact etiology of ATD remains unknown. Until now it is not clear whether bacterial infections can trigger ATD or modulate the efficacy of treatment and prognosis. The aim of our review is to characterize the microbiota and in ATD and to evaluate the impact of dysbiosis on treatment and prognosis. Moreover, variation of gut microbiome has been associated with thyroid cancer and benign nodules. Here we will characterize the microbioma in benign thyroid nodules, and papillary thyroid cancer to evaluate their implications in the pathophysiology and prognosis.